Volunteer First Responders for Optimizing Management of Mass Casualty Incidents. (4th June 2018) - Yafe, Eli; Walker, Blake Byron; Amram, Ofer; Schuurman, Nadine; Randall, Ellen; Friger, Michael; Adini, Bruria
ABSTRACT: Objective: Rapid response to a trauma incident is vital for saving lives. However, in a mass casualty incident (MCI), there may not be enough resources (first responders and equipment) to adequately triage, prepare, and evacuate every injured person. To address this deficit, a Volunteer First Responder (VFR) program was established. Methods: This paper describes the organizational structure and roles of the VFR program, outlines the geographical distribution of volunteers, and evaluates response times to 3 MCIs for both ambulance services and VFRs in 2000 and 2016. Results: When mapped, the spatial distribution of VFRs and ambulance stations closely and deliberately reflects the population distribution of Israel. We found that VFRs were consistently first to arrive at the scene of an MCI and greatly increased the number of personnel available to assist with MCI management in urban, suburban, and rural settings. Conclusions: The VFR program provides an important and effective life-saving resource to supplement emergency first response. Given the known importance of rapid response to trauma, VFRs likely contribute to reduced trauma mortality, although further research is needed in order to examine this question specifically. ( Disaster Med Public Health Preparedness . 2019;13:287–294)